Analisis Permasalahan Bagi Pihak Kreditur Dalam Jaminan Hak Atas Tanah Dengan Status Hak Guna Bangunan - Wiyard Yusuf Permana Agung; Noor Saptanti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The function of a banking institution is to provide credit services for the economic continuity of society. Loans given to debtors must be accompanied by collateral. One form of collateral is generally a certificate of land rights and one example is Building Use Rights (HGB). With this, there are many problems between debtors and creditors in handling collateral with the object of building use rights. Therefore, this legal research will discuss what problems arise when debtors provide building use rights guarantees to creditors (banks). This research uses a prescriptive normative research method with a statutory approach, a conceptual approach and a case approach based on the problems that occur. Based on this legal research, the author concludes that when the debtor guarantees the Building Use Rights, problems will arise for the debtor, namely the term of the HGB cannot be extended and the Building Use Rights can not be upgraded to Ownership Rights if the HGB is still encumbered with Mortgage Rights.